Dynamics of scalar fields from a generalized form of Lagrangian - Jaskirat Kaur; S.D. Pathak; Maxim Khlopov; Maxim Krasnov; Manabendra Sharma (Nuclear Physics B, 2025)
Scalar fields play a crucial role in Einstein's field equations, describing both the early- and late-time phenomenology of the universe. Despite numerous Lagrangians with distinct implications, a unified model has been lacking. We propose a generalized Lagrangian with two parameters, α and β, that encompasses quintessence, phantom, and tachyon fields. This framework captures their canonical dynamics, derives the background equations, and facilitates studies of cosmic evolution. Using the Om(z) diagnostic, we distinguish the evolutionary patterns of these fields from those of the cosmological constant, demonstrating smooth transitions between different behaviors. This cohesive structure enhances our understanding of dark energy and cosmic expansion, bridging theoretical versatility with observational constraints.